Análise das publicações sobre sífilis e herpes em perfis do instagram de veículos oficias de saúde no Brasil - Cordeiro, Annyelle Anastácio (2025)
Syphilis (acquired and congenital), herpes simplex, and herpes zoster are common sexually transmitted infections (STIs) and represent significant public health challenges in Brazil and worldwide. Therefore, it is essential that educational campaigns and health communication strategies utilize widely disseminated channels, such as social media, especially Instagram. This study aimed to analyze the communicative clarity of posts from official health agencies on Instagram addressing topics related to syphilis and herpes aimed at the general population. Publications were identified on 81 institutional profiles, including State Health Secretariats, Dental Associations and Councils, as well as the Ministry of Health. The posts were classified according to content type (educational actions, dissemination of epidemiological bulletins, combating fake news, and government campaigns), media format, thematic approach, number of posts (slides), likes, comments, and views. The clarity of educational posts was analyzed by four previously trained and calibrated researchers (Cohen’s Kappa intra- and inter-examiner ≥ 0.80), using the Brazilian version of the CDC's Clear Communication Index (BR-CDC-CCI), validated in 2020. The sample consisted of 200,402 publications, of which 520 addressed syphilis (acquired or congenital) and 44 herpes (simplex or zoster), resulting in two derived analysis plans. The posts were published between 2013 and 2024. State Health Departments were responsible for the majority of the content (syphilis: 82.5%; herpes: 40.9%). The most frequently addressed topics were acquired syphilis (68.9%) and herpes simplex (86.4%), with images being the most used format (syphilis: 84.6%; herpes: 84.1%). In a large part of the posts, the topic was only mentioned (syphilis: 59.0%; herpes: 72.7%), although most were educational in nature (syphilis: 50.2%; herpes: 84.1%). Communicational clarity, measured by the BR-CDC-CCI, was considered low for both topics (mean of 59.7%, SD = 18.3 for syphilis and 59.7%, SD = 18.1 for herpes). The average number of posts per publication was 2.34 (SD = 2.14) for syphilis and 2.18 (SD = 1.87) for herpes; The average number of likes was 394 (SD = 1186) and 597 (SD = 1853), respectively; and the average number of comments was 7.67 (SD = 27.5) for syphilis and 10.8 (SD = 42.9) for herpes. There was a positive and significant correlation between the BR-CDC-CCI score and the number of likes (r = 0.269; p ≤ 0.01), as well as between the score and the number of posts about herpes (r = 0.833; p ≤ 0.05). Posts produced by the Ministry of Health about syphilis showed greater communicational clarity (p < 0.01). In the case of herpes, carousel format posts (with two or more posts) and those with ≥ 105 likes obtained significantly higher clarity scores (p = 0.025 for both cases). Therefore, it is reinforced that, although official health agencies use Instagram as an educational tool for disseminating content about syphilis and herpes, the results of this study indicate low communication clarity. It is therefore necessary for these media outlets to invest in the production of clearer, more didactic content based on reliable sources, in order to broaden access to health information and ensure that educational messages reach the population in an understandable way.